Heat transfer modelling of flashlamp heating for automated tape placement of thermoplastic composites - Danezis, Anastasios; Williams, David; Edwards, Michael J.; Skordos, Alexandros A. (Cranfield University, 2021)
Heat transfer model validation: contains the experimental temperature data captured during the manufacture of AS4/PEEK composites and the corresponding model predictions.Irradiance profiles: contains the optical model predictions for the configuration used in the study and the data after the application of smoothing algorithm.Thermal model 2D geo: the geometry of the heat transfer model.Bulk profiles: contains the bulk profiles as predicted by the thermal model for the 25, 50, 100 Hz pulsed cases and continuous operation.
Keywords: 'Finite element analysis (FEA)'; 'Tape placement'; 'Process modelling'; 'Aerospace Materials'; 'Composite and Hybrid Materials'; 'Manufacturing Processes and Technologies (excl. Textiles)'